THE DYNAMICS OF CAPITAL FLOW AND PROCYCLICALITY OF FINANCIAL STABILITY SYSTEM IN ASEAN+3 - Yulia Indrawati; Adhitya Wardhono; Ciplis Gema Qo’riah; M. Abd. Nasir (UNEJ e-Proceeding)
The purpose of this study is to analyze the dynamics of the influence of capital flows and credit growth on macroeconomic stability in ASEAN + 3 countries. The analysis method used is panel vector error correction model during 2003-2014 and number of ASEAN member countries that are Brunei Darussalam, Cambodia, Indonesia, Lao PDR, Malaysia, Myanmar, Philippines, Singapore, Thailand, Vietnam, and added three countries namely China, Korea, and Japan. The variable used is Gross Domestic Product (GDP) annual percentage growth rate at market prices based on constant 2010 U.S. dollar, inflation annual consumer price in percentage, real effective exchange rate, net foreign direct investment (BOP in current US $), net portfolio investment (BOP in current US $), domestic credit provided by financial sector (% of GDP), central bank policy rate and discount rate. Sources of data were obtained from the World Bank and the International Monetary Fund. The analysis shows that capital inflows in the form of portfolio investments have an impact on economic growth in ASEAN + 3 countries compared to net foreign direct investment (FDI). This is because some ASEAN + 3 countries have a negative net FDI compared to net portfolio investment. The occurrence of friction in the credit market creates a pattern of procyclicality that is at the time of economic growth in the state of expansion or boom occurs high credit cycle without taking into account systemic risks and vice versa when the contraction or bust occurs credit crunch resulting in fluctuations in economic output.